2019
DOI: 10.1016/j.simyco.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy ofAspergillussectionFlaviand their production of aflatoxins, ochratoxins and other mycotoxins

Abstract: Aflatoxins and ochratoxins are among the most important mycotoxins of all and producers of both types of mycotoxins are present in Aspergillus section Flavi, albeit never in the same species. Some of the most efficient producers of aflatoxins and ochratoxins have not been described yet. Using a polyphasic approach combining phenotype, physiology, sequence and extrolite data, we describe here eight new species in section Flavi. Phylogenetically, section Flavi is split in eight clades and the section currently c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
387
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 405 publications
(439 citation statements)
references
References 260 publications
13
387
1
5
Order By: Relevance
“…6 Conventional identification approaches, including microscopic and macroscopic characterization, have been unable to discriminate between these closely related species. 6 Furthermore, a high degree of…”
Section: Amongmentioning
confidence: 99%
See 3 more Smart Citations
“…6 Conventional identification approaches, including microscopic and macroscopic characterization, have been unable to discriminate between these closely related species. 6 Furthermore, a high degree of…”
Section: Amongmentioning
confidence: 99%
“…The taxonomy of this section is complex and is currently under development . A large number of species in section Flavi are commonly observed plant pathogens producing several mycotoxins . The six economically important species in the section, A flavus , A parasiticus , A nomius , A oryzae , A sojae and A tamarii , are morphologically and phylogenetically very closely related; among them, A oryzae and A sojae are extensively used in the food and biotechnology industries .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of aflatoxins has been reported in members of three sections of Aspergillus genus; section Flavi (B-and G-type aflatoxins), section Ochraceorosei (aflatoxins B1 and B2), and section Nidulantes (formerly Emericella genus; aflatoxin B1) [8]. However, species of section Flavi are the most common and potent aflatoxin-producing moulds, with A. flavus and A. parasiticus being the most frequently encountered in agricultural products because of their widespread distribution in the agricultural environment and their versatility to grow and produce aflatoxins under different ecological conditions [9][10][11]. A recent classification based on a polyphasic approach revealed that 18 species out of 33 of the section Flavi are aflatoxigenic and that each of 16 species is able to produce the 4 major aflatoxins (AFB1, AFB2, AFG1, and AFG2), while the other 2 species produce either AFB1 alone (A. togoensis) or both AFB1 and AFB2 (A. pseudotamarii) [11] (Table 1).…”
Section: Aflatoxin-producing Molds: Taxonomical Elementsmentioning
confidence: 99%